Improving The Institution Of SelfRegulation In The Development Of The Market For Valuation Services In Uzbekistan (Eurasian Journal of History, Geography and Economics, 2025)
The article discusses the need to improve the institution of self-regulation based on international experience, the requirements for its membership, as well as the features of responsibility in the development of the market for appraisal services in the conditions of New Uzbekistan. At the same time, based on a generalization of foreign experience, a number of recommendations have been developed to improve the self-regulation of the appraisal services market in our country and to insure the risks of the professional activities of appraisers. This article discusses large-scale socio-economic reforms being implemented in the coming years as part of the further development of the appraisal services market in our country